Supplementation for athletes – part 1 – creatine - Paweł Błażej Szewczyk; Marcin Osowski; Bartłomiej Dorożyński; Ewa Szura (Farmacja Polska, 2023)
Creatine is an amino acid derivative, which play a key role in the process of energy production in human body. Creatine is synthetized with participation of 3 amino acids arginine, glycine and methionine and is accumulated as a free creatine and phosphocreatine (PCr), mainly in skeletal muscles. PCr is a high-energy phosphate source of energy, used during resynthesize of adenosine triphosphate (ATP), which is highly important during some stressful situations (e.g. physical activity, mental activity, health disorders/diseases) as well as in during the ischemia and/or hypoxia. Creatine supplementation can play a important role in modulating growth factors and increasing the potential of myosatelite cells formation, causing muscle tissue growth. The main sources of creatine in the diet, aside from supplementation, are animal products. Creatine levels in vegans are significant lower, than in the omnivores. The longest available on the market and the best examined chemical form of creatine is creatine monohydrate, which characterized by high bioavailability, high safety level and the numerous researches confirming its properties. Despite the multitude of creatine forms available currently on the market, there is no evidence confirming greater potential in increasing muscle creatine concentration during their supplementation. Creatine can be used in many sport disciplines, especially those characterized by high-intensity efforts, lasting up to 30 seconds The significant fluctuations of creatine levels are observed throughout life and during menstrual cycle in the females. It is associated with the frequency of various health disorders which severity and incidence rate seems to be possible to change by the creatine supplementation. The paper is a summary of the current knowledge and evidence regarding the role of creatine in human body, the possibility of its use as a dietary supplement, the supplementation protocols, doses and safety of use. It also gives answers to most frequently asked questions about creatine supplementation.